The Influence of Emotional Intelligence and Workload on Job Stress Among Personnel of the Bidpropam Division, Aceh Regional Police - Khairinnas, Khairinnas; Hardjo, Suryani; Indrawan, Yudistira Fauzy (Universitas Mercu Buana Jakarta, 2025)
The policing profession in Aceh Province presents distinctive operational, cultural, and psychological challenges that often generate high levels of occupational stress. This study explores how emotional intelligence and workload influence job stress among personnel of the Bidpropam Division at the Aceh Regional Police. Employing a quantitative cross-sectional design, data were collected from 119 officers between January and March 2025. The analysis confirmed that emotional intelligence contributes to reducing job stress, while workload tends to intensify it. Overall, the findings highlight that officers with stronger emotional regulation and interpersonal skills are more capable of coping with demanding work situations. The study underscores the importance of integrating emotional intelligence development into professional training and adopting effective workload management strategies to promote mental well-being and resilience within law enforcement institutions.